Respuesta :

[tex] \begin{cases}\large\bf{\green{ \implies}} \tt \: \frac{6}{5} \: k \: = \: 12 \\ \\ \large\bf{\green{ \implies}} \tt \: \frac{6k}{5} \: = \: 12 \\ \\ \large\bf{\green{ \implies}} \tt \: 6k \: = \: 12 \: \times \: 5 \\ \\ \large\bf{\green{ \implies}} \tt \: 6k \: = \: 60 \\ \\ \large\bf{\green{ \implies}} \tt \: k \: = \: \cancel\frac{60}{6} \\ \\ \large\bf{\green{ \implies}} \tt \: k \: = \: 10 \end{cases}[/tex]

Answer:

k = -10

Step-by-step explanation:

In order to solve for k, we need to isolate the variable. This means we need k to be on one side of the equation by itself.

We are given:

[tex]-\frac{6}{5}k=12[/tex]

The first thing I would do is multiply both sides of the equation by 5:

[tex](5)-\frac{6}{5}k=12(5)[/tex]

This leaves us with:

[tex]-6k=60[/tex]

Now, in order to get k by itself, we need to divide by -6 on both sides:

[tex]\frac{-6k}{-6}=\frac{60}{-6}[/tex]

Therefore:

[tex]k=-10[/tex]